(untitled) (Ciencia Veterinaria, 2022)
Analgesia y Anestesia Veterinaria : COMISION ACADEMICA Y CIENTIFICA MV. de Genaro, Mariana ( Práctica privada) Dr. Lorenzutti, Matías (Universidad Católica de Córdoba) Esp. Miguel, María Carolina (Universidad Nacional de La Pampa) Dr. Nejamkin, Pablo ( Universidad Nacional del Centro de la Pcia. de Buenos Aires) Dr. Otero, Pablo (Universidad de Buenos Aires) MV Robledo, Oscar ( Universidad Nacional de La Plata) Dr. Tarragona, Lisa (Universidad de Buenos Aires)